A BIBLIOMETRIC ANALYSIS OF MULTMEDIA LEARNING AND ENGLISH (2019-2025) - Siti Mastura Baharudin; Farida Mohamad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The advancement in multimedia has changed the education landscape, particularly after the COVID-19 pandemic. The new way of learning, both online and offline, has accelerated multimedia learning materials to enhance the quality of the learning experience. Significant changes have also been made in the teaching of the English language. Numerous literature topics on ’Multimedia learning and English’ have also grown flourishingly. However, more extensive bibliographic mapping studies are needed in this field. Raw data were extracted from the Scopus collection database between 2019 and the first quarter of 2025; after which, VOS viewer software was used to analyse the data. Specifically, the study scrutinized the following: research trends in multimedia learning and English, the most influential author, top contributing documents according to countries, the top contributing journal according to document type, and the top contributing journal documents according to subject area. It also includes complex techniques, such as co-occurrence of all keywords, co-occurrence by authors’ keywords, and co-citation citation of the authors. Overall, it was found that out of 1013 articles, 400 articles were selected for this study after refinement to only the English language, and exclusion of article reviews was made.